Positive Weighted Symmetry Function Kernels and Some Related Inequalities for a Generalized Class of Convex Functions. (17th May 2022) - Xiao, Yeliang; Shah, Ahsan Fareed; Zia, Tariq Javed; Bonyah, Ebenezer
Abstract : The fractional integral inequalities are crucial to deal applied problems. The present paper deals with the generalize midpoint type inequalities for a certain class of convex functions, namely, MT-convex functions in the setting of weighted fractional integral. It can be observed from the remarks given in the paper that our results or more generalized than existing results of literature and many of them can be obtained immediately from our results.